GLP-1 signaling is required for improvement of glucose tolerance by osteocalcin. Issue 2 (February 2020) - Mizokami, Akiko; Mukai, Satoru; Gao, Jing; Kawakubo-Yasukochi, Tomoyo; Otani, Takahito; Takeuchi, Hiroshi; Jimi, Eijiro; Hirata, Masato
Abstract : Osteocalcin is a bone-derived hormone that in its uncarboxylated form (GluOC) plays an important role in glucose and energy metabolism by stimulating insulin secretion and pancreatic β-cell proliferation through its putative receptor GPRC6A. We previously showed that the effect of GluOC on insulin secretion is mediated predominantly by glucagon-like peptide-1 (GLP-1) released from intestinal endocrine cells in response to GluOC stimulation. Moreover, oral administration of GluOC was found to reduce the fasting blood glucose level, to improve glucose tolerance, and to increase the fasting serum insulin concentration and β-cell area in the pancreas in wild-type mice. We have now examined the effects of oral GluOC administration for at least 4 weeks in GLP-1 receptor-knockout mice. Such administration of GluOC in the mutant mice triggered glucose intolerance, enhanced gluconeogenesis and promoted both lipid accumulation in the liver as well as adipocyte hypertrophy and inflammation in adipose tissue. Furthermore, inactivation of GLP-1 receptor signaling in association with GluOC administration induced activation of the transcription factor FoxO1 and expression of its transcriptional coactivator PGC1α in the liver, likely accounting for the observed upregulation of gluconeogenic gene expression. Our results thus indicate that the beneficial metabolic effects of GluOC are dependent on GLP-1 receptor signaling.